Study of the Effect of Magnetic Field on Dispersion of Crushed Portland Cement and Tensile Strength of Cement Stone - Ruslan Ibragimov; Evgenij Korolev; Evgeny Khorkov; Linur Gimranov (Salehan Institute of Higher Education, 2023)
This paper investigates the effect of a magnetic field on the grinding processes of Portland cement and the axial tensile strength of cement stone. It was found that the dispersion composition of Portland cement is affected by the magnetic field in two modes. Moreover, the grinding of Portland cement without a magnetic field has subtle modes within small particles (0.1–0.4 microns). The grinding of Portland cement with a magnetic field demonstrates an increase in the mode area of small particles and a decrease in the area of large particles (more than 1.6 microns), with an increase in processing time. In this work, the previously established magnetoplastic effect was confirmed in cement stone only in crystalline samples. The determined effect on cement stone is to reduce its strength by 53-59% and simultaneously increase relative deformation by 63–149%, depending on the specimen size and type. The magnetoplastic effect is also visually recorded on scans of the crack edges in cement stone examined using probe microscopy. The obtained experimental data confirm the validity of the proposed hypothesis of the effect of the magnetic field on polycrystalline materials with isotropic structure, in particular portland cement and cement stone, which consists in the fact that the magnetic field contributes to the accumulation of dislocations in the material, an acceleration of their movement, and the development of cracks. Doi: 10.28991/CEJ-2023-09-05-015 Full Text: PDF